Oligocene - Miocene Angiosperm fossil site in the Boa Vista Basin, Paraíba State, Northeast Brazil - SILVA, Cleide Regina Moura da (2024)
The Boa Vista Basin consists of a half-graben controlled by the extensional reactivation of the Serra do Monte Shear Zone, situated within the Transversal Zone, Alto Moxotó Domain of the Borborema Province. The basin was filled by a volcanic-sedimentary sequence characterized by basaltic flows, lacustrine bentonitic clays, and fluvial sandstones and conglomerates of the Campos Novos Formation. The age of the overlying basalts indicates the Oligocene-Miocene boundary. The palynomorph asso-ciation observed in the Campos Novos Formation presents a preliminary age from the upper Eocene to the lower Oligocene. We identified the fossil material in the sandstones and bentonitic clays. The mas-sive lithic arkosic sandstones present planar and trough cross-bedding and include pieces of silicified wood up to 2 m in length. The bentonitic clays present greenish, light brown, and dark brown colors, with fossil remains identified at the levels of greenish and light brown bentonitic clays in the Juá II and Bravo mines. About 200 specimens of leaves, fruits, and wood fragments were collected at these site, associated with ichnofossils in vertical and horizontal tubes. Among the numerous and varied leaf re-mains preserved as impressions, Fabaceae, Annonaceae, Lauraceae, Burseraceae, Anacardiaceae, Myrtaceae, and Malvales types dominate. The set attests to a tropical to subtropical flora, similar to elements that grow in the coastal areas of the state of Paraíba today. Some morphotypes are also characteristic of drier regions of Central Brazil. This set has preferential affinities with globally dry and locally humid environments. It seems to have a good relation with the more arid phases that ac-companied the global temperature drop intervals at the Oligocene-Miocene boundary, supporting the geological age data.